How much does Europe pay for clean air? - Miquel Oliu-Barton; Juan Mejino Lopez (Bruegel, 2024)
Despite significant progress, air pollution still causes exteuro600 billion in losses each year in the European Union - equal to 4 percent of its annual GDP. These costs stem from productivity losses such as increased absenteeism, the reduction of in-job productivity and harm to ecosystems. Air pollution costs are disproportionately high in eastern Europe and Italy, where losses are projected to remain above 6 percent of GDP until 2030. The EU's 10 percent most-polluted regions suffer 25 percent of the burden of mortality attributable to air pollution. Measures against air pollution should be prioritised, not delayed, in these regions. Promoting clean air boosts economic growth by exteuro50 billion to exteuro60 billion every year. The EU's increasing commitment to cleaner air is reflected by a threefold increase in the funds allocated to promoting clean-air policies, from exteuro7 billion annually for the period 2014-2020 to exteuro25 billion annually for 2021-2027, notably supported by the Recovery and Resilience Facility (RRF). EU financial support must continue beyond 2026 when the RRF terminates. The EU Ambient Air Quality Directive sends a strong signal but leaves loopholes: exceptions and postponements may jeopardise overall progress on cleaner air. Fossil-fuel consumption is one of the main obstacles to achieving clean-air targets. Yet fossil fuels subsidies were fourteen times higher than EU clean-air funds between 2014 and 2020, and are projected to remain five times higher for the years ahead. Ammonia, an important precursor of fine particulate matter mainly stemming from agriculture, is insufficiently regulated. Effectiveness of clean-air policies is context-dependent. Identifying concrete actions for each region and quantifying the potential gains are required to accelerate the transition to cleaner air. Phasing out coal use in residential heating is most profitable in eastern Europe, while reducing industrial and agricultural emissions would reap more benefits in the north of Italy.
Keywords: 330; European Green Deal; eu budget; climate change; decarbonisation